NGHIÊN CỨU QUÁ TRÌNH CACBON HÓA KHÔNG HOÀN TOÀN NGUỒN TINH BỘT NHẰM CHẾ TẠO XÚC TÁC ĐỂ TỔNG HỢP BIODIESEL TỪ DẦU HẠT CAO SU - Diệu Hồng, Nguyễn Khánh; Duy, Vũ Đình; An, Hoàng Lê; Diệu Linh, Nguyễn Thị (Vietnam Journal of Science and Technology, 2015)
Carbon based catalyst was prepared through partial carbonization of starch followed by sulfonation of product called “black powder” after the carbonization. The as-synthesized catalyst possessed very strong acid sites classified as a typical superacid assigned for –SO3H groups located by valance bonds on the catalyst surface. Some parameters such as carbonization temperature, time were controlled for optimizing the black powder properties and the catalyst activity. The catalyst was tested with rubber seed oil methanolysis in a batch process with reaction parameters such as temperature of 120oC, time of 5 hours, methanol/oil volume ratio of 1/1 and catalyst dosage of 10% oil weight. According to the partial carbonization optimizations, the conditions was temperature of 400oC, time of 90 minutes. The methyl ester yield after methanolysis was 95,8% proving favorable catalyst activity.